Grass Physiognomic Trait Variation in African Herbaceous Biomes. (28th January 2016) - Pasturel, Marine; Alexandre, Anne; Novello, Alice; Dièye, Amadou M.; Wélé, Abdoulaye; Paradis, Laure; Cordova, Carlos; Hély, Christelle
Abstract: African herbaceous biomes will likely face drastic changes in the near future, due to climate change and pressures from increasing human activities. However, these biomes have been simulated only by dynamic global vegetation models and failing to include the diversity of C4 grasses has limited the accuracy of these models. Characterizing the floristic and physiognomic diversity of these herbaceous biomes would enhance the parameterization of C4 grass plant functional types, thereby improving simulations. To this end, we used lowermost and uppermost values of three grass physiognomic traits (culm height, leaf length, and leaf width) available in most floras to identify several grass physiognomic groups that form the grass cover in Senegal. We then checked the capacity of these groups to discriminate herbaceous biomes and mean annual precipitation domains. Specifically, we assessed whether these groups were sufficiently generic and robust to be applied to neighboring (Chad) and distant (South Africa) phytogeographic areas. The proportions of two physiognomic groups, defined by their lowermost limits, delineate steppe from savanna and forest biomes in Senegal, and nama‐karoo, savanna, and grassland biomes in South Africa. Proportions of these two physiognomic groups additionally delineate the mean annual precipitation domains <600 mm and >600 mm in Senegal, Chad, and South Africa, as well as the <250 mm and >1000 mm domains in South Africa. These findings should help to identify and parameterize new C4 grass plant functional types in vegetation models applied to West and South Africa.